PENGARUH DESAIN, HARGA DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN PRODUK SEPATU BOLA SPECH LEGHTSPEED REBORN - M. Zamroji Almursyid; Zulkifli; Dian Irma Aprianti; Novel Reonald; Ahmad Surahman; Fathur Rahman (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2026)
This study aims to analyze the influence of design, product quality, and price on consumer satisfaction with Spech Lightspeed Reborn soccer shoes, a local brand that is growing in the domestic market. By using a quantitative approach and multiple linear regression method, this study collects data through questionnaires distributed to consumers who have used the product. This study addresses the competitive challenges in the local soccer shoe industry by evaluating the product dimensions that most affect consumer satisfaction. The results of the simultaneous test (F-test) indicate that the three independent variables together significantly affect consumer satisfaction. However, the partial test (t-test) reveals that only product quality and price have a significant influence, while design does not have a statistically meaningful impact. This indicates that although design is important as an initial attraction, consumer satisfaction is more determined by how well the product meets quality expectations and price suitability.The coefficient of determination value of 64.8% indicates that the model built is quite strong in explaining the variation in customer satisfaction. Product quality is the most dominant variable influencing satisfaction, followed by price. This has practical implications that producers should place more emphasis on improving product quality and competitive pricing strategies, rather than just focusing on design aesthetics. This research contributes to the development of marketing literature in the local sports product sector and serves as a reference for local brands in formulating product strategies based on consumer satisfaction. Furthermore, further studies are recommended to include other variables such as loyalty, promotion, or user experience to obtain a more comprehensive understanding of consumer behavior.